Strategi Pengembangan Peternakan Ayam Petelur Kecamatan Purbolinggo Kabupat,en Lampung Timur: Strategy For Development of Layer Chiken Farming in Purbolinggo Subdistrict, East Lampung Regency - Novita; Ivan's, Eny; Sari, Novia Ambar (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2023)
This study aims to evaluate the development strategy of laying hens in accordance with the area of ​​Purbolinggo District, East Lampung Regency. The analysis in this study uses several methods, namely matrix analysis of IFE and EFE (external and internal environment), and SWOT analysis. Based on the results of the SWOT analysis, the strategy for developing laying hens in Purbolinggo District, East Lampung Regency is a Growth and Build strategy (grow and develop) through an intensive strategy or integration strategy. The development of laying hens in Purbolinggo District, East Lampung Regency is in quadrant II on the I-E matrix indicating that the average internal condition and response to external factors is high. Extensive land owned by breeders has potential in the development of laying hens in Purbolinggo District, East Lampung Regency and is supported by local government policies so as to increase income and community welfare in a sustainable manner. Development strategies that can be implemented and prioritized for laying hens in Purbolingo District, East Lampung Regency are increasing production capacity, increasing livestock capacity, improving reporting systems and utilizing technology for promotion.